Rheology Study on Low‐Sugar Apple Jam by a New Nonlinear Regression Method of Herschel‐Bulkley Model. Issue 2 (6th June 2016) - Guo, Tongtong; Zhao, Kuo; Zhang, Zhaohui; Gao, Xin; Qi, Xiangming
Abstract: Structure break was found in shearing process of static prepared low‐sugar apple jam, which is a thixotropic and shear‐thinning fluid. In order to investigated this jam, a new nonlinear regression method of Herschel–Bulkley (H‐B) model without measuring yield stress was set up using R 2 as optimizing criterion, and compared with Casson model. Dynamic yield stress was calculated using the regression of downward curve. Casson model was found fit in high shear rate (in one case, R 2 0.9986, still lower than H‐B model, 0.9997). Break stress (from 113 to 497 Pa) could be largely increased by soluble solid concentration rising, and dynamic yield stress of H‐B model changed from 0.004 to 20.75 Pa, mainly depending on sugar and soluble solid concentration. Consistency index (24.50–102.3 Pa·s n ) was increased with adding soluble solid and decreased with adding sugar. Flow behavior index (0.229–0.363) was increased evidently with adding pectin and sugar. Practical Applications: The low‐sugar jams are more nutrition‐reasonable since they generally provide fewer calories, now short of deep research. Rheological properties are of great significance for processed food fluids. Traditional steady‐state test was applied widely in rheologic study of food fluids. However, information under flow curves could not be explored in detail because definition of yield stress was confused for a long time and the most common model of fluid, Herschel–Bulkley model, lacked suitable regression method. Additionally, upward curve was often ignored. In this work, a new simple nonlinear regression of Herschel–Bulkley model was set up without measuring yield stress investigated. Then the influences of ingredients on rheologic properties of low‐sugar apple jam could be investigated in detail. It is expected that the new method and observation would be applied by other rheologic researchers, and it is useful for finding relationships between mouth feel and indexes of Herschel–Bulkley model.